2017
DOI: 10.1038/s41598-017-06220-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic metabolic effects of Curcuma longa extract supplement in high-fructose and saturated fat fed rats

Abstract: The metabolic effects of an oral supplementation with a Curcuma longa extract, at a dose nutritionally relevant with common human use, on hepatic metabolism in rats fed a high fructose and saturated fatty acid (HFS) diet was evaluated. High-resolution magic-angle spinning NMR and GC/MS in combination with multivariate analysis have been employed to characterize the NMR metabolite profiles and fatty acid composition of liver tissue respectively. The results showed a clear discrimination between HFS groups and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 78 publications
3
8
0
Order By: Relevance
“…Namely, hepatic fatty acid profile was characterized by a higher proportion of MUFA, lower proportion of PUFA and increased oleic/stearic acid ratio (Δ9 desaturase index), regardless of stress. These results are in accordance with other animal studies using high-fructose diet [39][40][41]. In addition, it was previously demonstrated that fructose-induced increase of MUFA and decrease of PUFA in the liver were not accompanied by lipid accumulation and hepatic steatosis [39,40], but rather with increased secretion of triglycerides, as observed in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…Namely, hepatic fatty acid profile was characterized by a higher proportion of MUFA, lower proportion of PUFA and increased oleic/stearic acid ratio (Δ9 desaturase index), regardless of stress. These results are in accordance with other animal studies using high-fructose diet [39][40][41]. In addition, it was previously demonstrated that fructose-induced increase of MUFA and decrease of PUFA in the liver were not accompanied by lipid accumulation and hepatic steatosis [39,40], but rather with increased secretion of triglycerides, as observed in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, 3-hydroxibutyric acid (3-HB), a ketone body that represents the main alternative energy substrate to glucose and is a by-product of hepatic FA oxidation, was recovered in the rats of the HSuHF + BJ group. In agreement with previous studies [121,122], the reduced serum levels of 3-HB in HSuHF rats might suggest impaired FA metabolism and a degree of hepatic mitochondrial dysfunction since ketone bodies are produced from acetyl-Coa via ketogenesis, which mainly occurs in the hepatic mitochondria [8]. The recovery of 3-HB levels and the 3-HB/acetoacetate ratio in the rats of the HSuHF group when supplemented with BJ suggests an improvement in FA oxidation and mitochondrial function.…”
Section: Discussionsupporting
confidence: 89%
“…Betaine is an organic osmolyte in biological systems, which plays a key role in one of the methionine recycling pathways in the liver 22 and protects the body against osmotic stress. 20 Oxidation of choline to betaine occurs mainly in the mitochondria of liver cells via a series of enzymes.…”
Section: Discussionmentioning
confidence: 99%